MODEL OF BANKRUPTCY PREDICTION SERVICES COMPANY SECTOR RETAIL IN INDONESIA STOCK EXCHANGE (Study Case Period 2015 - 2017) - Indriani, Rina; Hakiman Thamrin (Dinasti International Journal of Digital Business Management, 2020)
This study aims to identify the dominant causes in forming a bankruptcy prediction model of retail trade service companies listed on the Indonesia Stock Exchange in the 2015-2017 period. The 2015-2017 observation period with a sample of 20 companies met the criteria as a sample. This research variable is divided into 2 namely dependent and independent variables. The dependent variable in this study is categorical data which is divided into two categories: unhealthy companies symbolized by the number 0 and healthy companies category symbolized by the number 1. The independent variables in this study are 20 financial ratios, among others, Current Ratio, Quick Ratio, Cash Ratio , Working Capital to Total Assets, Debt to Asset Ratio, Debt to Equity Ratio, Time Interest Earned, Working Capital Turn Over, Fixed Asset Turn Over, Receivable Turn Over, Total Asset Turn Over, Inventory Turn Over, Cash Turn Over, Cash Profit Margin, Operating Profit Margin, Gross Profit Margin, Return On Equity, Return On Assets, Return On Investment, Earning Per Share. The analytical method used is discriminant analysis. Discriminant Test Results using the stepwise method can be obtained variables that are selected as discriminator variables, namely the variable Debt to Equity Ratio, Return On Equity, and Earning Per Share to form discriminant functions as follows: R = - 3,197 + 0.292 Debt to Equity Ratio + 0.342 Return On Equity + 0.336 Earning Per Share The cut-off value in this study is 0 with a 75% prediction accuracy in unhealthy service companies and 73.3% in healthy service companies with an accuracy rate of 76.7% in retail trade service companies.